Cervical cytology by pap smear in reproductive population - Thobbi, Vidya A.; Khan, Farheen (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: The present hospital-based study was conducted to study the incidence of various cervical epithelial abnormalities such as infection, dysplasia and early cervical cancer changes in reproductive age population and its correlation with age, parity, socioeconomic status, clinical symptoms and cervical biopsy findings. Methods: A prospective study was conducted in 300 women of reproductive age group. The cervical smear was taken from all patients by means of the scrape technique using the Ayre’s spatula. Pap smear results were considered as positive (abnormal) when they are ASCUS, LSIL, HSIL or Invasive lesion. On persistence of unhealthy cervix/inflammatory smear after a course of antibiotic, direct cervical punch biopsy was taken. Results: Inflammatory smears were seen in 88.0%, ASCUS in 5%, LSIL in 1.4%, HSIL in 0.3% and invasive carcinoma in 0.3% patients. Direct cervical punch biopsy was taken from 13 cases out of 264 with inflammatory smear. Most of these patients had cervicitis (12 cases) while 1 case showed CIN stage 2. All cases of ASCUS and LSIL had infection which showed chronic cervicitis on biopsy. HSIL and Invasive carcinoma showed CIN stage 2 and Carcinoma as their biopsy findings. Conclusions: The Pap smear is a simple, safe, practical and cost-effective method for early detection of cervical cancer and its precursors. In developing countries like India, it is the most logical screening modality although it has a very low sensitivity, but detection rates could be further improved using liquid-based cytology and the use of endocervical cytobrush.